Final Solutions - Dattani, Mahesh (Gurugram Penguin Book, 2006)
Religion, is it the true final frontier, the great divide Is it conviction, hope or destitution Prevalent wisdom suggests that responses to omnipotent questions about religion are abundant but answers are scarce. Final Solutions and Mahesh Dattani attempt to set a platform to explore answers. The playwright suggests that religious fervor emanates from perceptions of being wronged and degrades to actions of doing wrong. Assigning blame only transitions to adopting blame. The fingers and their directions change, but they are always pointed. Hardika has witnessed 45 years of communal strife and distrust since the Partition, of India and Pakistan, in 1947. Ramnik, Hardika s son, with the tolerant psyche, has his own sensibilities driving his choices. Smita, the new generation and Hardika s granddaughter, is torn between familial impositions and personal liberal values. She questions the opinions and traditions she is expected to adopt. Aruna, the staunchly devout wife and Hardika s daughter-in-law, is most comfortable in the arms of her beliefs. Javed, the aggressive protector of Muslim rights is contrasted with Bobby, debunked and battered by self inflicted shame. The characters, by being cast in very opinionated and extreme personalities, strive to portray the emotions that drive communal distrust. Often right from their own perspective but disruptive when they collide. The naked honesty in the characters is evident as the progression of their personal and mutual conflicts morphs the stage into a veritable house of wax. Final Solutions is set in the early 1990s in northern India, with acutely perceptible throwbacks to the Partition in 1947. The play tactfully meddles into a world built on societal choices, political manipulations, personal beliefs, unbridled innocence, circumstantial belligerence, tolerant acquiescence and guilt ridden altruism.
Keywords: Literature- english; Sahitya Akademi awarded book